Management issues and concerns for internship students in China's hospitality industry: internship satisfaction and turnover intention - Liu, YanJun (2024)
Hotels are labour-intensive industries with intangible products, simultaneous production and consumption, and variable service quality etc. These characteristics determine the irreplaceable and important role of human resources in the development process of the hotel industry. As one of the three pillar industries of the tourism industry, the hotel industry has been facing a high staff turnover rate and low entry rate in recent years. In recent years, the hotel industry has been faced with a high staff turnover rate and a low entry rate, especially for front-line positions in the food and beverage, front office and guest room departments. In order to maintain normal operations, the employment structure of hotels has gradually changed. In order to maintain normal operations, the structure of the hotel's workforce has gradually changed, with many junior positions being replaced by interns. Interns are becoming a very important reserve of human They are becoming a very important reserve and a useful addition to the hotel's human resources. However, the willingness of hotel interns to stay in the industry after graduation is low. The willingness to stay in the industry after graduation is low. The internship experience constructs students' overall perception of the hotel industry and influences their willingness to enter the hotel industry after graduation. They also influence their willingness to work in the industry after graduation. Therefore, the issue of how to improve internship satisfaction and further increase the retention rate of students in the hotel industry has become a The issue of human resource management has become a focal point in the hospitality industry.